The potential of soil color properties to predict shallow slope failure in North-South highway slope, Malaysia - Othman, Rashidi; Hasni, Mohd Shah Irani; Shaharuddin, Ruhul Izzati; Hj. Baharuddin, Zainul Mukrim (2015)
Landslides in Malaysia have always been seen as serious issue and posed severe threats to any settlements and structures that support transportation, natural resources, as well as tourism. Eventhough the geology of Malaysia is quite stable, excessive development and urbanization leads to deforestation, weathering and erosion of the covered soil masses causing serious threat to slopes. The extent of damages could be reduced or minimized if a long-term early warning system predicting the landslide prone areas would have been in place. A study was carried along the North-South highway, Malaysia. 60 points consists of stable and unstable slope were visited and soils samples were collected from those stations for laboratory analysis. All the selected slopes for soil sampling are from class 5 (40-50 degree). The aim of the research is to identify the soil color properties to be manipulated as indicator to forecast shallow slope failure. In conclusion, the indicator to predict shallow slope failure is ranged from 5YR to 10YR based on Munsell soil color chart. The hues that indicate stable slope are between 2.5 YR - 5YR while the hues that indicate unstable slope are between 5YR -10YR. This is due to the high contents of clay and sand which affect the soil color to yellowish, red and whitish.